FOREIGN LANGUAGE TRAINING STUDENTS OF ENGINEERING SPECIALITIES THROUGH IMPLEMENTATION OF THE CONTEXT APPROACH - Galina A. Krasnoshchekova (Открытое образование (Москва), 2016)
This article presents a model of foreign language professionally-oriented training of future engineers, and the creation of the new foreign language teaching programs is justified. The author determines the content of the main methods and forms of teaching foreign languages. It is proved that the proposed educational technology, which implements the context approach to teaching students of technical institutes, joins together all the components of the training content, explaining the advisability of forming skills and contributes to the quality of language training of future engineers, as well as the acquisition of the real experience in professional activity.